Implementation of the SSCS Learning Model to Improve Student Learning Outcomes on Data Presentation Material in Elementary School - Lilis Saputri Handayani; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This study aims to improve student learning outcomes by implementing the Search, Solve, Create, and Share (SSCS) learning model on data presentation material in grade IV of elementary school. This study uses a classroom action approach implemented in two cycles, with stages of planning, implementation, observation, and reflection. The subjects of the study were grade IV students of SD Negeri Mernek 03. Data collection techniques were done through written tests to measure student learning outcomes. The results of the study indicate that the implementation of the SSCS learning model can improve student learning outcomes from cycle I to cycle II. Thus, the SSCS learning model is effective for use in mathematics learning, especially in data presentation material.